Body image predictors of depressive symptoms in adolescence. (December 2018) - Murray, Kristen; Rieger, Elizabeth; Byrne, Don
Abstract: Introduction: Depression rises significantly in adolescence, with females reporting twice the prevalence of males into adulthood. In accordance with cognitive vulnerability theories, eating and weight-related disturbances have been implicated in this increase, but a broader assessment of body image constructs within this framework is needed. Methods: The current prospective study examined body importance, body dissatisfaction, and body change strategies to lose weight and increase muscularity as predictors of depressive symptoms over one year in N  = 298 adolescents in Canberra, Australia (at Time 2, the sample comprised n  = 161 female adolescents, M age  = 15.36 years, SD  = 1.10; n  = 137 male adolescents, M age  = 15.54 years, SD  = 1.15). The moderating role of sex was also assessed. Results & conclusions: Results revealed that body importance and body change strategies to increase muscularity explained significant variance in depressive symptoms beyond baseline covariates of depressive symptoms and stress, with the effect of body importance relevant in female but not male adolescents. The findings support the use of more comprehensive assessments of body image constructs to inform cognitive vulnerability theories of adolescent depression, and corresponding prevention and intervention programs.